Strategic management and development of human potential in the Provincial Municipality of Huanuco, Peru, 2021 - Lara-Tapia, María I. (2023)
Objective. To determine the influence of strategic management on the development of human potential in the Provincial Municipality of Huánuco, 2021. Methods. The approach of the study was quantitative, while the research was explanatory and applied. The population consisted of 235 administrative workers working in the Provincial Municipality of Huanuco, while the sample consisted of 136 workers. Results. A total of 25.7 % considered the strategic management of the Provincial Municipality of Huánuco to be deficient, 64.7 % perceived it to be regular and 9.5 % perceived it to be good. 30.8 % perceived that the development of the human potential of the Provincial Municipality of Huanuco is poor, 57.3 % perceived it to be fair and 11.7 % expressed that it is good. Conclusion. It was determined that Spearman's rho between the variables "strategic management" and "development of human potential of administrative personnel" is 0.540. Thus, according to Spearman's correlation estimation scale, there is a moderate positive correlation and, in addition, the data has a significance level of 0.016, which is less than 0.05, indicating that the correlation is significant. It can be concluded that strategic management is having a moderately significant impact on the development of human potential in the Provincial Municipality of Huanuco, 2021.